Selective Effects of mTOR Inhibitor Sirolimus on Naïve and CMV-Specific T Cells Extending Its Applicable Range Beyond Immunosuppression - Bak, Szilvia; Tischer, Sabine; Dragon, Anna; Ravens, Sarina; Pape, Lars; Koenecke, Christian; Oelke, Mathias; Blasczyk, Rainer; Maecker-Kolhoff, Britta; Eiz-Vesper, Britta (Frontiers in Immunology, 2018)
Cytomegalovirus (CMV) infection/reactivation remains among the most important complications of immunosuppression after transplantation. However, recent clinical observations indicate that mammalian target of rapamycin (mTOR) inhibition with sirolimus may improve the outcome of CMV complications. Underlying mechanisms of this observation, particularly the effect of sirolimus on naïve- and CMV-specific cytotoxic CD8+ T-cell (CMV-CTL) functionality is still undiscovered. Here, the influence of sirolimus on naïve and memory CMV-CTLs was determined by CD3/CD28 crosslinking and alloreactivity assays. After stimulating CMV-CTL with HLA-A*02:01-restricted CMVpp65-peptide loaded artificial antigen-presenting cells (aAPCs), we measured the effect of sirolimus on T-cell proliferation, phenotype and functionality. Sirolimus significantly improved CMV-specific effector memory T-cell function and negatively influenced naïve T cells. This unique mechanism of action was further characterized by increased secretion of interferon-gamma (IFN-), granzyme B (GzB) and enhanced target-cell-dependent cytotoxic capacity of activated CMV-CTLs. Next-generation-sequencing (NGS) was applied to monitor T-cell receptor (TCR)-repertoire dynamics and to verify, that the increased functionality was not related to sirolimus-resistant CTL-clones. Instead, modulation of environmental cues during CMV-CTL development via IL-2 receptor (IL-2R)-driven signal transducer and activator of transcription-5 (STAT-5) signaling under mTOR inhibition allowed fine-tuning of T-cell programming for enhanced antiviral response with stable TCR-repertoire dynamics. We show for the first time that sirolimus acts selectively on human naïve and memory T cells and improves CMV-specific T-cell function via modulation of the environmental milieu. The data emphasize the importance to extend immune monitoring including cytokine levels and T-cell functionality which will help to identify patients who may benefit from individually tailored immunosuppression.